What Can Museum Anthropology Do in the Twenty-first Century? - Philipp Schorch (Museum & Society, 2024)
This article sets out to tackle the question: ‘what can museum anthropology do in the twenty-first century?’ It does so by focusing on the doing in a double-sense: on what museum anthropology can do, as in affecting, impacting and achieving, as well as on museum anthropology’s own doing, as a particular set of knowledge practices brimming with methodological, epistemological and ontological potentials to be harnessed for its own renewal and for cross-disciplinary fertilization across the academy and beyond the museum itself. The character of the article is programmatic, laying out the program of museum anthropology being developed at LMU Munich, Germany. The article begins by pondering this question explicitly. Then it proceeds by mapping out what has been done, what is being done, and what will be done to address this question at LMU Munich in collaboration with other universities and museums. At the end, the article draws out some of the implications of answering that question for an anthropology not only of and in but through museums, which intervenes in the fields that it studies.